PLANEJAMENTO E ALOCAÇÃO OTIMIZADA DE PÁTIOS PARA EXPLORAÇÃO EM PLANOS DE MANEJO FLORESTAL SUSTENTÁVEL NA AMAZÔNIA - GOUVEIA, DÉBORA MONTEIRO (2023)
Forest companies are constantly searching for quality, productivity and cost reduction. Planning supported by tools that help in decision-making with an integrated view of operations are important strategies to guarantee forest management. Among the activities, the dimensioning, location and opening of roads, skid trails and storage yards cause a lot of expenses. The objective of this study was to evaluate the existing infrastructure for forestry operations and to propose an optimized model for the allocation of wood storage yards in forests subject to a sustainable management regime in the Amazon. The study was carried out in a forestry company, located in the state of Pará, in an annual production unit with an area of 3,556.27 hectares. Initially, in Chapter I, the quantity and dimensioning of the infrastructures approved by the environmental agency in the forest management plan were compared with their respective modifications that occurred in the execution of the forest exploitation. The analyzed results show an increase in the density of roads, yards and in the maximum skidding distance. The forest management carried out, both in its planning and in its execution, was in accordance with the legislation norms, however analyzing the use of these infrastructures it is suggested that their allocation can be better optimized. Later in Chapter II, based on these results, two models were analyzed using mixed integer linear programming. Model A - without penalties and Model B - with cost penalties. The model identifies optimal yard allocation locations, governed by distance constraints and maximum stocked volume. 311 possible storage yards were allocated to meet the demand for 16.425 exploitable trees. The results were evaluated by means of the Euclidean tree-yard distance and by the planning of forest exploitation. In the analysis, Model A performed better in terms of reducing the sum of displacement distances between trees-yards. Model B performed better in the uniformity of the amount of wood to be stored and in the reduction of impacts caused by the opening of this infrastructure. It was possible to conclude that the solution found by these models is a path of less accumulated damage, certainly viable solutions that can be adopted by the company.